A clinician-monitored 'PTSD Coach' intervention: findings from two pilot feasibility and acceptability studies in a resource-constrained setting. Issue 2 (19th December 2022) - Bröcker, Erine; Olff, Miranda; Suliman, Sharain; Kidd, Martin; Mqaisi, Busisiwe; Greyvenstein, L.; Kilian, Sanja; Seedat, Soraya
ABSTRACT: Background: The high prevalence of trauma exposure and consequent post-traumatic stress disorder (PTSD) is well documented in low- and middle-income countries, and most individuals with PTSD have limited access to treatment in these settings. Freely available internet-based interventions, such as PTSD Coach (web-based and mobile application), can help to address this gap and improve access to and efficiency of care. Objective: We conducted two pilot studies to evaluate the feasibility, acceptability, and preliminary effectiveness of PTSD Coach in a South African resource-constrained context. Method: Pilot 1: Participants with PTSD ( n  = 10) were randomized to counsellor-supported PTSD Coach Online (PCO) or enhanced treatment as usual. Pilot 2: Participants ( n  = 10) were randomized to counsellor-supported PTSD Coach Mobile App or self-managed PTSD Coach Mobile App. Feasibility and acceptability were assessed by comparing attrition rates (loss to follow-up), reviewing participant and counsellor feedback contained in fieldnotes, and analysing data on the 'Perceived helpfulness of the PTSD Coach App' (Pilot 2). PTSD symptom severity was assessed with the Clinician Administered PTSD Scale for DSM-5 (CAPS-5), changes between treatment and control groups were compared, the reliable change index (RCI) was calculated, and clinically significant changes were determined. Results: Three participants in Pilot 1 and two participants in Pilot 2 were lost to follow-up. Fieldnotes indicated that PTSD Coach Mobile App addressed identified computer literacy challenges in Pilot 1 (PCO); and a shorter duration of intervention (from 8 to 4 weeks) was associated with less attrition. The RCI indicated that four participants in Pilot 1 and eight participants in Pilot 2 experienced significant improvement in PTSD symptom severity. Conclusions: The preliminary results suggest that both platforms can alleviate PTSD symptoms, and that the involvement of volunteer counsellors is beneficial. The use of PTSD Coach Mobile App may be more feasible than the online version (PCO) in our setting. HIGHLIGHTS Research on supported PTSD Coach interventions is limited in resource-constrained settings. Both volunteer counsellor-supported PTSD Coach Online and the PTSD Coach Mobile App showed preliminary reliable and clinically significant changes. The use of PTSD Coach Mobile App seems more feasible than the volunteer counsellor-supported PTSD Coach Online.